STUDY ON PEDOLOGICAL SOIL PROPERTIES IN THE “HANEȘ” MINE AREA FOR ITS REMEDIATION - CHIRILĂ BĂBĂU, Adriana Mihaela; MICLE, Valer; SUR, Ioana Monica (Studia Universitatis Babeș-Bolyai Ambientum, 2018)
Pollution has become an issue of current concern for all humanity, because of the negative impact on the environment and human health. One of the most affected by environmental factors due to human activities is the soil, which is a sponge for contaminants. Soil contamination with heavy metals presents a major concern both global and national levels, in order to control resulted pollutants from industrial activities and finding different methods of eco-friendly and effective remedy. In the present paper is presented the Haneș mine area, the soil from here being very acid due to mining activities performed in the past.